Wild Indian [videorecording (DVD)] - Corbine, Lyle Mitchell, Jr; Corbine, Lyle Mitchell, Jr; Corbine, Lyle Mitchell, Jr; Greyeyes, Michael; Spencer, Chaske; Eisenberg, Jesse, 1983- (Vertical, 2021)
Decades after covering up the murder of his classmate, an Ojibwe man has moved on, changing his name, finding a respectable job and a beautiful wife, when suddenly he crosses paths with a man who shares his violent secret and seeks vengeance.